2016
DOI: 10.1210/jc.2015-3284
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Steroidogenic Characteristics of Aldosterone-Producing Adenomas With ATPase orCACNA1DGene Mutations

Abstract: APAs with ATPase mutations demonstrated a potentially severe primary aldosteronism phenotype, whereas those with CACNA1D mutations displayed characteristics similar to wild-type APAs. The status of stimulated aldosterone production was also different according to the cell types, suggesting that the regulatory effects of adrenocorticotropic hormone on aldosterone synthesis could possibly vary according to the intracellular signaling involved in hormone production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Large multicenter studies have confirmed these findings and have shown that these mutations (G151R and L168R) account for 34%-47% of APAs in people of European ancestry (8)(9)(10) and 60%-77% of people of Asian ancestry (11)(12)(13)(14), with differences likely attributable to differences in disease definition. There is also a striking sex dimorphism in European and some Asian cohorts (8,10,11,15,16); European cohorts consistently show that these mutations account for 50%-60% of women with APAs, but only 20% of men, and KCNJ5 mutations are more prevalent in younger patients (8,10).…”
Section: Introductionmentioning
confidence: 77%
“…Large multicenter studies have confirmed these findings and have shown that these mutations (G151R and L168R) account for 34%-47% of APAs in people of European ancestry (8)(9)(10) and 60%-77% of people of Asian ancestry (11)(12)(13)(14), with differences likely attributable to differences in disease definition. There is also a striking sex dimorphism in European and some Asian cohorts (8,10,11,15,16); European cohorts consistently show that these mutations account for 50%-60% of women with APAs, but only 20% of men, and KCNJ5 mutations are more prevalent in younger patients (8,10).…”
Section: Introductionmentioning
confidence: 77%
“…The diagnosis was confirmed by endocrinologic examinations, such as the furosemide plus upright test, saline-loading test, and captopril-loading test [8][9][10]. All subjects were diagnosed with unilateral APA by computed tomography imaging and segment-selective ACTH loading adrenal venous sampling (SS-ACTH-AVS), as reported previously [9][10][11][12]. All subjects underwent unilateral adrenalectomy.…”
Section: Study Populationmentioning
confidence: 98%
“…With the exception of one Taiwanese patient who exhibited a Tyr410Asp substitution (404), all mutations identified thus far involve the deletion of one or more amino acids between Thr-423 and Leu-433 lying in the M4 region of the plasma membrane, believed to be important in Ca 2ϩ binding during its transport to the extracellular space. Clinically APAs containing ATP2B3 mutations are associated with higher levels of aldosterone secretion when compared with wild-type APAs (27,186,397), most likely as a result of an observed increase in aldosterone synthase CYP11B2 expression (250,254,396). Recently these associations have been confirmed through the transfection of ATP2B3 carrying the common Leu425_Val426 deletion into adrenocortical NCI-H295R cells, resulting in impaired Ca 2ϩ clearance accompanied by elevated basal Ca 2ϩ , CYP11B2 expression, and aldosterone secretion (370).…”
Section: Pmca3 Cerebellar Ataxia and Adenomamentioning
confidence: 98%
“…However, what is more surprising is that two novel ATP2B3 mutations have recently been found in tissue from a number of aldosterone-producing adenomas (APAs), a major factor in the development of primary aldosteronism which is the most common cause of secondary hypertension (27). Since Beuschlein et al's first report in 2013 (27), ATP2B3 mutations have been identified in APAs present in western European, Japanese, Taiwanese, Chinese, and American populations occurring at frequencies ranging from 0.6 to 9% (6,102,121,186,272,330,331,396,404,422). With the exception of one Taiwanese patient who exhibited a Tyr410Asp substitution (404), all mutations identified thus far involve the deletion of one or more amino acids between Thr-423 and Leu-433 lying in the M4 region of the plasma membrane, believed to be important in Ca 2ϩ binding during its transport to the extracellular space.…”
Section: Pmca3 Cerebellar Ataxia and Adenomamentioning
confidence: 99%